2000
DOI: 10.1074/jbc.275.20.15535
|View full text |Cite
|
Sign up to set email alerts
|

The Yap1p-dependent Induction of Glutathione Synthesis in Heat Shock Response of Saccharomyces cerevisiae

Abstract: Glutathione is synthesized in two sequential reactions catalyzed by ␥-glutamylcysteine synthetase (GSH1 gene product) and glutathione synthetase (GSH2 gene product). The expression of GSH1 in Saccharomyces cerevisiae has been known to be up-regulated by Yap1p, a critical transcription factor for the oxidative stress response in yeast. The present study demonstrates that GSH2 expression is also regulated by Yap1p under oxidative stress-induced conditions. In addition to oxidative stress, expression of GSH1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
1
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 48 publications
(48 reference statements)
7
82
1
1
Order By: Relevance
“…GSH1-lacZ expression was elevated by ϳ2-and 3.5-fold upon oxidative stress induced by H 2 O 2 or diamide, respectively, in the presence of wild-type Yap1p, consistent with the findings of other groups (28,30). Expression of C629A Yap1p increased GSH1 expression by 2-fold in the absence of oxidant, and this expression failed to increase in the face of H 2 O 2 exposure and was only modestly enhanced during diamide stress.…”
Section: Differential Role Of the Yap1p C Terminus In Oxidative Stresssupporting
confidence: 79%
“…GSH1-lacZ expression was elevated by ϳ2-and 3.5-fold upon oxidative stress induced by H 2 O 2 or diamide, respectively, in the presence of wild-type Yap1p, consistent with the findings of other groups (28,30). Expression of C629A Yap1p increased GSH1 expression by 2-fold in the absence of oxidant, and this expression failed to increase in the face of H 2 O 2 exposure and was only modestly enhanced during diamide stress.…”
Section: Differential Role Of the Yap1p C Terminus In Oxidative Stresssupporting
confidence: 79%
“…Hence, ycfR induction may be related to a general effect of all the stresses or to the common mechanisms that the cells use to protect themselves against stress, as seen in plants (23), Saccharomyces cerevisiae (76), and bacteria (32); for example, it has been shown that both heavy metal stress (23) and heat shock stress (76) converge in the generation of oxygen-reactive species.…”
Section: Discussionmentioning
confidence: 99%
“…Several genes responsible for glutathione metabolism, such as glutathione synthesis (GSH1 and GSH2) and glutathionedependent antioxidant systems (GPX2 and GLR1), are up-regulated by Yap1 (19,25,55,58,67). In addition to its antioxidant function, glutathione is important in detoxifying many harmful xenobiotics.…”
mentioning
confidence: 99%